PELATIHAN APLIKASI MENDELEY PADA MAHASISWA UNIVERSITAS HALU OLEO - Sri Suryana Dinar; Andi Muh. Ruum Sya'baan; Fahruddin (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2024)
Mendeley is a useful application that attempts to integrate a "citation & reference manager" into a social network. Mendeley reference management makes it easier for users to compile bibliography lists for writing scientific papers and Mendeley makes it easier for researchers to find fellow researchers through a network in the Mendeley menu. The objectives of this research are (1) To improve participants' abilities in compiling and searching bibliography using reference management using Mendeley (2) To improve participants' abilities in compiling and searching tables of contents using Mendeley (3) To find out participants' responses to training activities. Methods in service (1) Observation method, (2) Lecture method, (3) Training method. The results of the Mendeley-based reference management training were very effective in providing knowledge value, especially to students when they wanted to write journals/proposals and theses. Judging from the results of the training after being given the material, practice and assistance, it was stated that 85% of the students were very easy to implement the material that had been obtained by operating the Mendeley application directly, both based on Mendeley Web and Mendeley Desktop. Search and enter references easily, create citations both manually and automatically.